Impact of drought-tolerant rice varieties (DTRV) on the livelihood of smallholder farmers - CGIAR Research Program on Rice (2019)
Adoption of DTRV increased the rice yield by 570 kg/ha (24% increase) leading to an increase in income of US$ 126 per ha in Benin, Madagascar and Nigeria. Adoption also improved household food security.